Cognitive function in dyslipidemia patients: exploring the impact of statins - Wang, Wenxiao; Li, Xin (Frontiers in Neurology, 2024)
Background Evidence regarding the relationship between the use of statins and cognitive outcomes presents varying findings. This study aims to analyze the relationship between sustained statin use and cognitive performance in dyslipidemia patients. Methods This study presents findings from the Beijing Ageing Brain Rejuvenation Initiative (BABRI) study, in which a cohort of community-dwelling dyslipidemia patients (Entire sample, N = 1,062, aged 50–86) was recruited. Participants were divided into two groups based on their sustained use statins (Statins group, N = 677) or not use any lipid-lowering agents (Untreated group, N = 385). Furthermore, the entire sample was stratified by age into the middle-aged sample (N = 451) and the older people sample (N = 611), following a similar categorization based on statin application. ANCOVA was used to evaluate the relationship between sustained statin use and cognitive function. Results Overall, in the total sample, the statins group demonstrated better cognition in overall cognition, memory, visuospatial ability, attention, executive function, and language domains compared to the untreated group. Moreover, the statins group only showed better performance in attention among the middle-aged sample. In the older people sample, statins group exhibited superior cognitive performance across various cognitive domains compared to untreated group. Conclusion Among dyslipidemia patients in Beijing community, sustained statin users exhibited superior cognitive function across all domains compared to untreated individuals, with particularly noticeable improvements among those aged 65 and above. These findings underscore the protective effect of statins on cognitive function in dyslipidemia patients, highlighting significant benefits for the older people population.